If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1-4w=-6w-3
We move all terms to the left:
-1-4w-(-6w-3)=0
We get rid of parentheses
-4w+6w+3-1=0
We add all the numbers together, and all the variables
2w+2=0
We move all terms containing w to the left, all other terms to the right
2w=-2
w=-2/2
w=-1
| 30+b=37 | | t=t/3-1 | | 5(2p-6)=-49p-3) | | 2.5+0.3x=-8.4 | | -5+g=3g+9 | | 2x+5+4=9x+20 | | 6+f=-10+3f | | 8.25x=2542.94 | | X+5÷x-1=4 | | -5p=-6p+6 | | 4x^2+28^3=0 | | 26-3n=8 | | −b=8 | | -2(8-y)=(-6y) | | 18x-11x=63 | | 4m+9=2m-3 | | 3(6-4x)=-29^x-9) | | 2(3x+5)=5(x−7) | | 18=22-6g | | 4z+33=67 | | 6x-35=3x-53=180 | | 10+5x=7(2)-4 | | 6x*(4-x)=-2x*(3x-1)+14x | | 5r+-6r+20r+5r–19r= | | 8x+12=5x-+6 | | 12x+75x+21=630 | | 3b=75 | | 6x+43x+2=2x+1⩾-3x+6 | | 3x-50=7x+38 | | 8(a+6)+2=2a-4 | | 14=(2/3)(9x-15) | | 6(m-1)=9m+15 |